Language assessment literacy in university admission policies, or the dialogue that isn't. (July 2019) - Deygers, Bart; Malone, Margaret E.
Research in the field of Language Assessment Literacy (LAL) shows that university admission officers and policy makers are not generally well-versed in matters of LAL. Only very few studies to date have traced why this may be the case, however, and in the field of language testing few studies to date have reported on how university admission language requirements are set. Nevertheless, because of the impact of test use on university admissions, developing such knowledge is essential to the progress of LAL as a discipline. This paper reports on a qualitative study that includes all university admission policy makers in one context (Flanders, Belgium). The analyses of the interviews show that the concerns and ideas of LAL scholars and those of university admission policy makers may differ substantially. Real-world policy is determined by pragmatism and compromise and policy makers, even at universities, may fail to consider empirical findings. Because this study shows that the view of policy makers can be quite dissimilar from the traditional approach taken in the LAL literature, the authors argue that it may be as beneficial to encourage policy literacy among language testing professionals, as to expect LAL from policy makers.